The supposed shame of aging female bodies and the saving grace of transience. Issue 4 (16th September 2019) - Lelwica, Michelle Mary
Abstract: Where does the supposed shame of older women's bodies come from? In this essay, I suggest that such shame is not a natural response to aging; rather, it is a culturally conditioned reaction to the patriarchal fantasy of female physical perfection. While certain norms and narratives within Christianity tacitly encourage women to pursue this fantasy, there are also resources within this tradition that can help us challenge the stigma assigned to older female flesh and affirm the goodness of bodies that have lived a long time. Simultaneously, aging itself can provide a lens for fruitfully rethinking some central Christian ideas.